Financial System Stabilization in Islamic Economics Perspective - Yuana Tri Utomo; Syafiq Mahmadah Hanafi; Juliana Juliana; Anggrismono Anggrismono (Perhimpunan Intelektual Muslim Indonesia, 2023)
The purpose of this study is to find a picture of a stable financial system from the perspective of the Islamic economy. This type of research is literature research with qualitative methods using normative, historical, and phenomenological approaches. The normative approach is used to explain the concepts of Islamic economics. The historical approach is used to explain the chronology of the use of the current financial system. The phenomenological approach explains contemporary events related to the research topic. The data is taken from a wide variety of literature, such as the Qur'an, al-Hadith, and many articles from national and international reputational journals related to this research topic. Researchers used more than 50 articles from Scopus quartile indexed journals 1 to 4 in the last five years. The collected data are analyzed by a deductive method, that is, the process of data analysis of the general opinion of Islamic teachings that have been agreed upon by the majority of people and then narrowed down to a specific idea of the stability of the financial system in Islam. The results of this study were found due to the instability of the current financial system because it uses the concept of usury (in Arabic, usury). In contrast, usury in Islamic economics is legally haram. Therefore, the way to stabilize the financial system from an Islamic economic perspective is to use gold and silver currency standards, abolish the practice of usury, and supervise the turnover of money in society by the hisbah. This research can add to the academic discourse of Islamic economics.